Croatia - Grace, Lucie; Mutić, Anja; Putinja, Isabel (Lonely Planet Global Limited, 2024)
Lonely Planet's Croatia is our most comprehensive guide that extensively covers all the country has to offer, with recommendations for both popular and lesser-known experiences. Walk the city walls in Dubrovnik, discover marvellous Mljet, and hit the beach in Bol; all with your trusted travel companion.